2019
DOI: 10.29103/ijevs.v1i2.1526
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Google Classroom in ELT

Abstract: Google Classroom is to offer a platform of blended learning in schools in order to simplify creating assignments and getting the grade out to the students in a paperless way. There are many facilities provided by Google classroom, they are: it will make easier for teachers to carry out learning activities, the intended learning is not only in class, but also outside the classroom because students can learn wherever and whenever by accessing google classroom online. Subject that relating to discuss as in the mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
74
0
12

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 104 publications
(117 citation statements)
references
References 0 publications
1
74
0
12
Order By: Relevance
“…It is one way that schools and teachers can offer students e-learning which is attractive to students, while teacher learning is a process that is transformed into virtual classes. Sukmawati & Nensia (2019) stated that this research helped students better understand using Google classroom by decision-makers of higher education organizations. It is assumed that helped to measure the student awareness of the technology mentioned previously.…”
Section: B Review Of Literaturementioning
confidence: 99%
“…It is one way that schools and teachers can offer students e-learning which is attractive to students, while teacher learning is a process that is transformed into virtual classes. Sukmawati & Nensia (2019) stated that this research helped students better understand using Google classroom by decision-makers of higher education organizations. It is assumed that helped to measure the student awareness of the technology mentioned previously.…”
Section: B Review Of Literaturementioning
confidence: 99%
“…Google Classroom is a Google product that connects to Gmail, drive, hangout, YouTube, and the deep calendar. The many facilities provided by google classroom will make it easier for teachers to carry out learning activities (Sukmawati & Nensia, 2019). There are four benefits of the Google Classroom application, first, Google Classroom has the potential to minimize or shorten communication and workflows for students by providing an access point to a series of discussions and assignments; second, the Google Classroom application can help students to keep their documents more organized, because all work or assignments can be saved easily with no paper required.…”
Section: Introductionmentioning
confidence: 99%
“…Besides this, students can also interact with each other in the online space. It is concluded that Google classroom has an important role in English learning and teaching [15].In Google Classroom, teachers can freely hand out a scientific assessment and provide an independent assignment to the students.…”
Section: E-learning Platformsmentioning
confidence: 99%